KRITERIA PEMIMPIN DALAM PERSPEKTIF HADITS - Abdul Malik Ghozali; Subhan Abdullah Acim (istinbath, 2018)
The issue of leadership is considered important and still actual becauseit is very influential on the progress of civilization and human prosperity. Onthe other hand, Islam adhered to by most humans is a religion of totality,which governs aspects of human life. Including aspects of leadership in onecountry and nation. One source of Islamic teachings is the Prophet’s guidancein the form of hadith. The hadith of the Prophet (s) is the second source inthe teachings of Islam after the Qur’an. So it needs to be revealed about theexplanation of the Prophet related to the criteria of the leader.This study attempts to answer some key questions: What is the Islamic viewof leadership? What is the criteria of leaders in the perspective of the hadith ofthe Prophet? To answer this question, research is done by examining the textsof the hadith of the Prophet. The text of this hadith is examined in variousapproaches; theological, historical, philosophical, tafsir, hermeneutical, andjurisprudence. The method of content analisys was originally carried out onthe text of the Qur’an and hadith and clerical explanations of the hadith text.Hadith matan (text) searched by takhrij and internal critic (naqd dakhili), afterdoing external critic (naqd khariji) toward hadith transmission.From this study, it is concluded that: First, the leadership part of the missionof Islamic teachings. This is evidenced by the hadiths of Prophet SAW whoreviewed the criteria of leaders. Second, the themes contained in these hadithsinclude 11 themes of criteria of leaders; Responsibility, honesty, simplify notcomplicate, not authoritarian, public servant and social caring, be fair, holdfast to religion, do not regard skin color, do not pursue position (ambitious),skillful and intelligent, soul stability. Third, from the 14 narrations of the hadithof this leader’s criterion, fairness is summarized in three different narrations.This indicates that a fair theme is a central issue of the leader’s criteria inIslam. Isu kepemimpinan dianggap penting dan masih aktual karena sangatberpengaruh pada kemajuan peradaban dan kemakmuran manusia. Di sisi lain,Islam agama yang dianut oleh sebagian besar manusia adalah agama totalitas,yang mengatur aspek kehidupan manusia. Termasuk aspek kepemimpinandalam satu negara maupun bangsa.Salah satu sumber ajaran Islam adalahpetunjuk Nabi dalam bentuk hadits.Hadits Nabi SAW yang merupakan sumberkedua dalam ajaran Islam setelah al-Qur’an.Maka perlu diungkap tentangpenjelasan Nabi SAW terkait kriteria pemimpin.Penelitian ini mencoba menjawab beberapa pertanyaan pokok: Bagaimanapandangan Islam tentang kepemimpinan? Bagaimana kriteria pemimpin dalamperspektif hadits Nabi?Untuk menjawab pertanyaan ini, penelitian dilakukandengan mengkaji teks-teks matan hadits Nabi. Teks matan hadits ini dikajidengan berbagai pendekatan; teologis, historis, filosofis, tafsir, hermeneutis,fikih.Metode content analisys pada awalnya dilakukan terhadap teks al-Qur’anmaupun hadits dan penjelasan ulama terhadap teks hadits. Matan haditsdilakukan takhrij dan kajian naqd dakhili, setelah melakukan naqd kharijiterhadap sanad hadits.Dari kajian ini disimpulkan bahwa ;Pertama, kepemimpin bagian dari misiajaran agama Islam. Hal ini terbukti dengan adanya hadits-hadits Nabi SAWyang mengulas tentang kriteria-kriteria pemimpin.Kedua, Tema-tema yangterkandung dalam hadits-hadits ini meliputi 11 tema kriteria pemimpin;Tanggung jawab, jujur, mempermudah tidak mempersulit, tidak otoriter,pelayan rakyat dan peduli sosial, bersikap adil, berpegang teguh dengan agama,tidak memandang warna kulit, tidak mengejar jabatan (ambisius), cakap dancerdas, kestabilan jiwa. Ketiga, dari 14 riwayat hadits kriteri pemimpin ini,sifat adil terangkum dalam tiga riwayat yang berbeda.Hal ini mengindikasikanbahwa tema adil merupakan isu sentral kriteria pemimpin dalam Islam.